Synergistic Attenuation of the TNF-α/NF-κB Inflammatory Axis in Colorectal Carcinogenesis: Lactococcus lactis D4 as a Mucosal-Protective Adjuvant to Capecitabine - Leonard Khriestsandi Saleh; M Iqbal Rivai; Rini Suswita; Irwan; Avit Suchitra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Capecitabine serves as a standard chemotherapeutic agent for colorectal cancer, but its clinical efficacy is frequently hindered by severe gastrointestinal toxicity and incomplete suppression of the inflammatory tumor microenvironment. We evaluated the synergistic potential of Lactococcus lactis D4, a probiotic strain isolated from traditional fermented buffalo milk, as an immunonutritional adjuvant to Capecitabine in a 1,2-dimethylhydrazine-induced colorectal cancer rat model. Methods: Sprague-Dawley rats were maintained on a standardized AIN-93G diet and induced with 1,2-dimethylhydrazine. Animals were randomized into Negative Control, Cancer Control, L. lactis D4 monotherapy, Capecitabine monotherapy, and Combination therapy. Treatments were administered for 14 days. We assessed cachexia, macroscopic microadenoma multiplicity, and TNF-α expression utilizing immunohistochemistry. Synergy was mathematically validated using the Coefficient of Drug Interaction. Results: The Combination group significantly prevented chemotherapy-induced cachexia, demonstrating a 2.1% weight gain compared to a 4.5% weight loss in the Capecitabine monotherapy group (p < 0.05). Macroscopic microadenomas were rapidly reduced in the combination group. Furthermore, the combination therapy synergistically suppressed colonic TNF-α protein expression (Coefficient of Drug Interaction = 0.83). Additionally, L. lactis D4 entirely mitigated capecitabine-induced mucositis. Conclusion: L. lactis D4 functions as a highly potent adjuvant to Capecitabine. It prevents cachexia, protects mucosal architecture, and exerts a mathematically proven synergistic suppression of the TNF-α inflammatory axis.